Push-off reactions in recovery after tripping discriminate young subjects, older non-fallers and older fallers - Pijnappels, Mirjam; Bobbert, Maarten F.; Dieën, Jaap H. van (Gait & posture, 2005)
Tripping is a major cause for falls, especially in the elderly. This study investigated whether falls in the elderly can be attributed to inadequate push-off reactions by the support limb in the recovery after a trip. Twelve young (20–34 years) and eleven older (65–72 years) men and women walked over a platform and were tripped several times over an obstacle that suddenly appeared from the floor. Kinematics and ground reactions forces of the support limb during push-off were measured of falls and successful recoveries. Young subjects did not fall. The older subjects were divided into a group of four non-fallers and seven fallers. Older fallers showed insufficient reduction of the angular momentum during push-off and less proper placement of the recovery limb. This was due to a lower rate of change of moment generation in all support limb joints and a lower peak ankle moment. Onset of knee moment generation was slightly delayed in older fallers. Improvement over trials was ascribed to better positioning of the recovery limb, as no clear differences were seen in the joint moments of the support limb. In conclusion, the contribution of the support limb to prevent a fall after tripping is decreased in older adults. Lower limb strength could be an underlying factor and strength training might help to reduce fall risk.